Atypical lobular endocervical glandular hyperplasia: two case report and literature review - Wan, Ziqing; Liu, Shuang; Sang, Na; Tang, Yi; Wen, Peng; Zhang, Pu; Shu, Chuqiang (Frontiers in Oncology, 2023)
Atypical lobular endocervical glandular hyperplasia (ALEGH) is considered a precancerous lesion of gastric-type adenocarcinoma (GAS)/minimal deviation adenocarcinoma (MDA) characterized by an insidious onset, atypical symptoms, and often negative human papillomavirus (HPV) screening. Early screening for this disease is challenging, leading to a high rate of missed clinical diagnoses and the development of malignant tumors at the onset. Increased vaginal discharge and the presence of imaging cystic masses at the internal cervical ostium are often observed in patients with ALEGH. Therefore, we reviewed the clinical data of two cases of ALEGH that were identified and diagnosed in the early stages at our hospital. Through a comprehensive analysis of the medical history and diagnosis plan, combined with a review of relevant literature, to improve the early recognition and diagnosis of ALEGH, as well as strengthen the management of cervical precancerous lesions.